Stomach Content Analysis of Hemiramphodon pogogthatus from University of Riau Aquatic Ecosystem - Supiana, Supiana; Putra, Ridwan Manda; Windarti, Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract            Hemiramphodon pogognathus is one of freshwater fish that inhabit the Freshwater University of Riau. To understand the stomach content analysis of this fish, a study has been conducted from November-December 2017. The analisys was conducted using volumetric method. Sampling was conducted once/week for a month period. There were 66 fishes captured. Stomach content of the fish was anlyzed as a basis to calculate the Preponderance index (PI).Result shown that the main food ofH. pogognathus is insects (PI 98.85%) debris (PI 0.73%) and plant (PI 0.78%). Based on the data obtained, this fish can be catorized as carnivore. Keyword: Stomach content, Hemiramphodon pogognathus, Index of PreponderanceCarnivore,